Monitoring of Litigation Costs and Efforts to Eradicate Judicial Corruption Practices - Aditya, Zaka Firma; Al-Fatih, Sholahuddin (Indonesian Journal of Advocacy and Legal Services, 2020)
Judicial corruption practices in Indonesia have been going on for long time. Even, according to the Transparency International survey (2007), the judiciary in Indonesia ranks the highest for corruption perception index. Not only that, the mode used by the judicial mafia is also increasingly modern and occurs almost in all aspects of judiciary. This research has two aims, namely: (1) to know and analyze the mode of corruption in the judicial process in Indonesia, and (2) to know and analyze the model of litigation cost control in the judicial process in Indonesia. This research is a juricial-normative research which is using the statute approach and conceptual approach. From this research, it can be seen that, typically, corrupt practices have been initiated since the registration of the case, the establishment of the judges panel, summoning witnesses and experts, negotiating decisions and costs of copy of the decisions. Ironically, many parties are involved in the judicial corruption practices ranging from clerks, officials and employers in the judiciary and the judges themselves. However, the more modern technology can be used as an alternative solution in combating the practices of judicial corruption. One of them, by applying litigation cost control that can be integrated through a whistleblowing system. In this way, the public can monitor in real-time the trial process starting from registration litigation fees, the process of litigation until post-verification, officials and employers in the judiciary and the judges themselves.